The relationship between the use of Meta-cognitive Self Regulated Learning Strategies (Meta-SRLS) and achievement in English language learning - Mahadi, Rozilawati (2019)
This study provides a detailed description of Meta-cognitive Self Regulated Learning (Meta-SRL) strategies employed by one hundred and seventy (170) undergraduate students majoring in different Engineering courses at one local university in the northern part of Malaysia. The findings revealed that the proposed Meta-SRLS framework can be used as a basis for a development of assessment instruments and teaching curricula that measure and develop a systematic Meta-cognitive Self Regulated Learning ability among ESL learners. The findings also indicated the use of a wide range of Meta-cognitive Self Regulated Learning Strategies (Meta-SRLS) by the participants in their English language learning. Moreover, the results of Pearson correlation test also revealed a positive relationship between the use of Meta-SRL strategies and the participants‟ level of English language proficiency. The results affirmed the findings of previous studies that language learners with advanced proficiency level tend to utilize more strategies than those with low proficiency level (e.g., Magogwe & Oliver, 2007); Hong-Nam & Leave ll, 2006; Wharton, 2000; Oxford & Nyikos, 1989; O‟Malley & Chamot, 1985).